Kajian Kepustakaan : Metode Latihan Fisik Terhadap Peningkatan Kebugaran Jasmani Remaja - Oktaviana, Nuraini; Jariono, Gatot; Indarto, Pungki (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2024)
This study aims to identify physical exercise methods that can improve adolescent physical fitness. The study used a literature study method by analyzing articles from various scientific journals published between 2014 and 2024. The results showed that interval, circuit, and plyometric training methods are effective in improving adolescent physical fitness. This exercise increases strength, endurance, and flexibility. This study provides recommendations for adolescents to exercise regularly to maintain physical and mental health. Exercise recommendations include daily activities such as walking, cycling, jogging, and swimming. Support from parents and the environment is very important to ensure that adolescents remain physically active. In conclusion, exercise methods improve adolescents' physical fitness Keywords: adolescents, exercise method, Physical fitness, physical exercise.